Label-free single microparticles and cell aggregates sorting in continuous cell-based manufacturing - Gong, Lingyan (2024)
There is a paradigm shift in biomanufacturing toward continuous bioprocessing but cell-based manufacturing using adherent and suspension cultures, including microcarriers, hydrogel microparticles, and 3D cell aggregates, remains challenging due to the lack of efficient in-line bioprocess monitoring and cell harvesting tools. Herein, a novel label-free microfluidic platform for high throughput (≈50 particles/sec) impedance bioanalysis of biomass, cell viability, and stem cell differentiation at single particle resolution is reported. The device is integrated with a real-time piezo-actuated particle sorter based on user-defined multi-frequency impedance signatures. Biomass profiling of Cytodex-3 microcarriers seeded with adipose-derived mesenchymal stem cells (ADSCs) is first performed to sort well-seeded or confluent microcarriers for downstream culture or harvesting, respectively. Next, impedance-based isolation of microcarriers with osteogenic differentiated ADSCs is demonstrated, which is validated with a twofold increase of calcium content in sorted ADSCs. Impedance profiling of heterogenous ADSCs-encapsulated hydrogel (alginate) microparticles and 3D ADSC aggregate mixtures is also performed to sort particles with high biomass and cell viability to improve cell quality. Overall, the scalable microfluidic platform technology enables in-line sample processing from bioreactors directly and automated analysis of cell quality attributes to maximize cell yield and improve the control of cell quality in continuous cell-based manufacturing.